Soldiers as Workers: Class, Employment, Conflict and the Nineteenth-Century Military - MacKay, Lynn (Labour / Le Travail, 2017)
The article reviews the book, "Soldiers as Workers: Class, Employment, Conflict and the Nineteenth-Century Military," by Nick Mansfield.